Analisa Dan Implementasi Security Mail Server - Daniel Adi Putra Sitorus; Yulia Fatma; Harun Mukhtar (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
Mail server is one of the most widely used server functions in the company. This discusses e-mail itself which can reduce mailing costs, is more efficient than manual communication and can be used as attachments that are useful as a supplement and additional documents related to the contents of e-mail. Zimbra is a mail server application that provides complete features and also makes it easy to install mail server management, also mail server security issues are a factor that must be considered by the system administrator. The security design for e-mail servers addresses the importance of being able to prevent spam e-mail attacks that can fill e-mail servers and make mail server performance faster. Because a good mail server security can optimize the performance of the mail server itself. In this final project, the work and implementation of the zimbra mail server security will be carried out specifically for handling email spam. The zimbra email server will analyze its security against spam email attacks, so that it can function as an email server on the company.